2021
DOI: 10.3389/fphar.2021.670151
|View full text |Cite
|
Sign up to set email alerts
|

Kun-Dan Decoction Ameliorates Insulin Resistance by Activating AMPK/mTOR-Mediated Autophagy in High-Fat Diet-Fed Rats

Abstract: Background: Metabolic syndrome is characterized by central obesity, hyperglycemia and hyperlipidemia. Insulin resistance is the leading risk factor for metabolic syndrome. Kun-Dan decoction (KD), a traditional Chinese medicine, has been applied to treat patients with metabolic syndrome for over ten years. It is increasingly recognized that autophagy deficiency is the key cause of metabolic syndrome. Therefore, we aimed to explore whether KD can activate autophagy to improve metabolic syndrome.Methods: Network … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Therefore, AMPK-mediated phosphorylation of ULK1 is critical for inducing mitophagy ( Trefts and Shaw, 2021 ) ( Figure 3A ). Seabright et al ( Seabright et al, 2020 ) recently found that AMPK activation promotes mitophagy by increasing mitochondrial fission and autophagy without the PINK1/Parkin pathway, and AMPK/mTOR activation improves IR, which has been demonstrated in many studies ( Wang et al, 2020 ; Zhu Y. et al, 2021 ; Su et al, 2021 ).…”
Section: Introductionmentioning
confidence: 90%
“…Therefore, AMPK-mediated phosphorylation of ULK1 is critical for inducing mitophagy ( Trefts and Shaw, 2021 ) ( Figure 3A ). Seabright et al ( Seabright et al, 2020 ) recently found that AMPK activation promotes mitophagy by increasing mitochondrial fission and autophagy without the PINK1/Parkin pathway, and AMPK/mTOR activation improves IR, which has been demonstrated in many studies ( Wang et al, 2020 ; Zhu Y. et al, 2021 ; Su et al, 2021 ).…”
Section: Introductionmentioning
confidence: 90%
“…All chemical ingredients from the eight herbal medicines of JPYSF were collected from an online database, including a traditional Chinese medicine system pharmacology database and an analysis platform (TCMSP, https://tcmspw.com/tcmsp.php ), Integrative Pharmacology-based Research Platform of Traditional Chinese Medicine (TCMIP) v2.0 ( Xu et al, 2019 ; Su et al, 2021 ), and previous pieces of literature ( Wang F et al, 2020 ). All chemical ingredients were employed to evaluate the degree of drug absorption based on the criteria of oral bioavailability (OB ≥ 30%) and drug-like (DL ≥ 0.18) (mean value for all molecules within the DrugBank database).…”
Section: Methodsmentioning
confidence: 99%
“…BSAconjugated palmitic acid increases Akt/mTORC1 pathway via GPR40, and the mechanism by which palmitic acid regulate mTORC1 activity is probably its translocation onto lysosomal membranes [136,137]. Moreover, oleic acid activates Akt/mTORC1 and ERK/mTORC1 pathways via GPR40 or GPR120 [138], and inhibits AMPK signaling which is a negative regulator of mTORC1 [139][140][141][142]. There are few reports on stearic acid and mTORC1 activity, it can upregulate mTOR expression [143].…”
Section: Lcfa Sensing By Mtorc1mentioning
confidence: 99%
“…The downstream signaling pathways mediated by GPR40 or GPR120, the second messenger cAMP can activate downstream effector PKA and regulate ERK sequentially [138,146,147], and another downstream pathway PLC/DAG/IP3 in which DAG can excite PKC and ERK/mTORC1 [147,148], and IP3 leads to calcium release activating AMPK which is an upstream negative regulator of mTORC1 [139,140,142,149], and the third downstream pathway, PI3K/Akt pathway, can activate mTORC1 signaling [136,138,140,147]. Different G proteins mediate LCFAs to regulate mTORC1 signaling.…”
Section: Lcfa Sensing By Mtorc1mentioning
confidence: 99%